A lelkészi munkavégzés határkérdései – Kiselőadás - MAKKAI, László (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2023)
Boundary Issues of Pastoral Work – Workshop In this work, I discuss the boundary issues of pastoral work. I am convinced that the competence of priests/pastors is limited to a certain level. We must be able to recognize our limits and at the same time experience the process of development. There are two sides of the personal well-being of pastors. One is the existence of ideal pastoral accompaniment competencies, which means meeting the criteria of a mature professional personality. Another point is to see through the illusion of perfection to form a realistic image of what a “good enough” pastor can be like. The way to do this is if the studies, practical experiences, and experiences that enrich the personality grow into the pastor’s work, constantly keeping in mind that by accepting the help and guidance of others, if necessary, he is able to turn his own shortcomings and weaknesses into resources.